Prospects and Potential of Bradyrhizobium diazoefficiens Based Bio-Inoculants on Soybean Production in Different Agro-Ecologies of Mozambique - Savala, Canon Engoke Norris; Wiredu, Alexander Nimo; Chikoye, David; Kyei-Boahen, Stephen (Frontiers in Sustainable Food Systems, 2022)
Soybean production in sub-Saharan Africa is increasing as farmers open more land area for cultivation or replace other crops such as tobacco in favour of this legume crop. Despite production increases in Mozambique, demand for animal feed and oil is not satisfied. As such farmers explore ways to improve yield per unit area of soybean by using bio-inoculants from various sources and agroecological adaptability. These bio-inoculants are seldom available during planting time, and retail at almost similar prices although yields remain varied based on the product source, handling, and the rhizobia strain carrier. Mozambique does not produce bio-inoculants, so it obtains the product from neighbouring countries or as far as the South American continent. In this study we evaluated the performance, ecological adaptability, and soybean productivity of seven Bradyrhizobium diazoefficiens strain-based bio-inoculants from several countries with different carrier materials, Biofix, Masterfix, Nitrofix, NitroZam, N-Fixer, Soygro (peat and liquid) against a control on two soybean varieties Storm and TGx 1904-6F. The trial was conducted in 2016 and 2017 growing seasons in three agroecologies of Mozambique at Angonia, Nampula and Ruace. Data on nodulation, plant growth, biomass nitrogen content at beginning of podding (R3) stage, yield and yield components of soybean were evaluated. Nodule weight per plant increased variedly with inoculation for both varieties where Storm ranged from 7.7 mg (check) to 141.2 mg for Masterfix while TGx 1904-6F was check 14.7 mg to 167.6 mg for Masterfix across environments. Plant tissue nitrogen content at R3 stage was higher in inoculated non-promiscuous variety at 3.9% than the promiscuous counterpart with 3.7%. Storm, a non-promiscuous short maturity soybean responded to inoculation and accumulated more N than the medium to late maturity promiscuous TGx 1904-6F. Both Storm and TGx 1904-6F responded to all inoculants variedly with NitroZam yield of 2750 kg ha-1 highest while Soygro Liquid lowest with 2051 kg ha-1 but more than check with 1690 kg ha-1 across sites. There were varietal differences in 100-seed weight after inoculation where Storm (15.4 g) had heavier seeds than TGx 1904-6F (13.1 g). Inoculation improved plant growth and development, increased nodulation, and soybean yield.